Right of Child In Broken Home Family At Mitch Albom's The First Phone Call From Heaven (2013) Novel: Individual Psychological Approach - Istighfaroh, Melia (2016)
The study is about the right of child in broken home family reflected in Mitch Albom's the first phone call from heaven. The purpose of this study is to analyze the major's character personality based on the individual psychological perspective. In analyzing this novel, the researcher uses individual psychological approach and qualitative method. This research is using two data sources, namely primary and secondary data. The primary data source is the written data of the novel in form of words, phrases, sentences, paragraphs and dialogues, while the secondary data is taken from the information needed. The data collection method in this research is using qualitative method. The analysis of Sullivan Harding begins with the analyze of his inferior feeling and compensation, striving for superiority, style of life, creative power, social interest, and fictional finalism. Then, the researcher discusses the right of child in broken home family that occurs in Sullivan Harding. According to the analysis, Sullivan Harding is a grown up with lack of interaction with society, social withdrawal, and he also hardly believes for something that immaterial like spiritual things. Although his children right's were not directly abused, but there were preventions by his parent for him to express his actual desire and needs, especially in term of education right and right to speak. Sullivan Harding had been detained for exercising his freedom of expression.